Linguistic Means of Homeland Characterization in M. A. Asturias’s Mister President - Davitova, Nuriya R. (2021)
The present research is devoted to the concept ‘patria’ (homeland) analysis in the Nobel Prize-winning Guatemalan writer Miguel Angel Asturias’s novel El señor presidente (Mister President). The verbalizations of the studied concept in the novel are counted and their linguistic context is analysed. The totalitarian society described by the writer is not fully fictional. The dictatorship of Estrada Cabrera, though unnamed in the novel, is depicted. The linguistic realization of the studied concept is based on two groups of antithesis. The perception of homeland by real patriots, who are now considered the traitors of their homeland, and that of the people, who conform to the current conditions, but it is obvious that they are the ones who are ready to betray. The second antithesis is the fear of the president and calling the president the honoured citizen, the father and the defender of the homeland. The analysis of the linguistic means used to verbalize the concept ‘homeland’ in the studied novel shows that the said concept can be used by a totalitarian society as a tool of manipulation. Further analysis of the concept ‘homeland’ in other literary works by the authors writing in Spanish and belonging to different Hispanic countries will reveal the linguistic differences of the national variants of Spanish.